Renal Transplantation in Hepatitis C Positive Patients: A Single Centre Experience - P. R. Shah; A. V. Vanikar; M. R. Gumber; H. V. Patel; V. B. Kute; S. M. Godara; H. L. Trivedi (Journal of Transplantation)
Introduction. Hepatitis C virus (HCV) infection is an independent risk factor for renal transplantation (RTx). Immunosuppression minimization can render better quality of life to these patients. Methods. We analyzed 132 HCV-positive RTx patients (group A) transplanted under tolerance induction protocol (TIP) and compared them with 79 controls (group B) transplanted using standard triple drugs. TIP consisted of 1 donor-specific transfusion, peripheral blood stem cell infusion, portal infusion of bone marrow, and target-specific irradiation. Their immunosuppression was cyclosporin, 2 ± 1 mg/kg BW/day + prednisone, 10 mg/day. Results. TIP had no side effects. Although unequal in size, the groups were well balanced. Group A patient survival at 1, 5, and 10 years was 92.4%, 70.4%, and 63.7%, respectively, versus 75.6%, 71.7%, and 55.7% in later, and graft survival was 92.9%, 81.5%, and 79.1% versus 91.7%, 75.7%, and 67.7%, respectively. Mean serum creatinine (mg/dL) at these time periods in former was 1.38, 1.72, and 1.87, versus 1.3, 1.75, and 2.1 in later. Altered liver functions were noted in 22% patients in former versus 31% in later. Group A had lesser rejection episodes. Conclusion. RTx using TIP in HCV-positive patients is a viable option with acceptable outcome.